2019
DOI: 10.29333/jisem/5893
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Predictive Model Based Prototype for Student Drop-out in Secondary Schools

Abstract: When a student is absent from school for a continuous number of days as defined by the relevant authority, that student is considered to have dropped out of school. In Tanzania, for instance, drop-out is when a student is absent continuously for a period of 90 days. Despite the fact that several efforts have been made to improve the overall status of education at secondary level, the student drop-out problem still persists. Taking advantage of advancement in technology, several studies have used machine learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The model's purpose was to aid education stakeholders in detecting at-risk students and schools. This developed system can be used by authorities for planning and budgeting to satisfy school requirements [16]. Combining models always achieve best accuracy than individual models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model's purpose was to aid education stakeholders in detecting at-risk students and schools. This developed system can be used by authorities for planning and budgeting to satisfy school requirements [16]. Combining models always achieve best accuracy than individual models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors report an accuracy of 88.8% using the C4.5 algorithm. The work of Mduma et al (2019) focuses on the use of artificial intelligence in developing an ensemble predictive based prototype to help education stakeholders in the early detection of student dropout in secondary schools. Using a dataset from Tanzania from 2015 consisting of 61,340 instances their model combines logistic regression and multilayer perceptron models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies in African countries also show that students' dropout was an issue. The Ghana Statistical Service (GSS) carried out a survey that showed that as high as 25% of youth who should be in Senior High School are not in school (Yusuf, 2019); the rate of student dropout in Tanzanian secondary schools is about36% (Mduma, 2019). The Kenyan government intended to make education affordable and accessible to all children in Kenya (Musangi et al, 2017) as well as address the low completion rates (Oprong, 2016) through free primary education (FPE) and free day secondary education (FDSE).…”
Section: Introductionmentioning
confidence: 99%